Organizing principles, habitus and family practices - Poeschl, Gabrielle Anny (2018)
The importance attributed to social insertions in Doise’s perspective of social representations and Bourdieu’s notion of habitus are discussed and illustrated by a set of studies on family practices showing the effect of social positions on social representations and social practices. Findings reveal a consensus about what the family tasks are and who is undertaking them. They show that men and women agree to find the unequal distribution of family work fair and the traditional differentiation of family roles between husband and wife desirable. The level of education triggers variations in the belief in sex differences, the representations on family work, and spouses’ actual contribution to family tasks, without threatening the asymmetrical positions of men and women in society.